Galicia and Portugal: snippets of our common history - López Mira, Álvaro Xosé (Madrygal. Revista de Estudios Gallegos, 2012)
It´s really surprising for us the lack of systematic treatment among professional historians about the beaten path –politicals, socials, economics…– tours of Galicia and Portugal across the centuries. It seems that although some modern historiography tries to free stiff corsets previous interpretations, respectful prejudice still prevails regarding the respective histories of nation-building differentiated, like the myths that often they were based, were more consistent for the scientific paradigm than the certainty provided by the historical facts themselves.
Keywords: Gallaecia; partition; Portugal; Galicia; history; nation; nation-building.